The Burden of Blood-Pressure-Related Cardiovascular Mortality in Mexico - Dora E. Cortés-Hernández; Krista J. Lundelin; Esteban Picazzo-Palencia; Juan J. de la Cruz; José J. Sánchez; José R. Banegas (International Journal of Hypertension)
This study shows that in Mexico, a country at an advanced stage in the epidemiologic transition, with the national burden of disease dominated by noncommunicable diseases, elevated blood pressure is a major clinical and public health problem. 31.7% of the Mexican individuals aged 50 and over had systolic hypertension, and 47.3% were at systolic prehypertensive levels. Also, approximately half of all cardiovascular deaths that occurred annually in the population of Mexico aged ≥50 years are attributable to above optimal levels of systolic blood pressure. We think these estimates may help order health priorities in Mexico (and other middle-income countries) at a time when the costs of medical care take a considerable share of the gross national product in most countries.